Metal Catalyzed Cascade Reactions - Müller, Thomas J.J.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2006)
Transition metal-catalyzed cascade reactions are an elegant approach to complex molecular scaffolds. Besides their esthetics and increase in structural complexity, they have also become mechanistic challenges for the combination of organometallic elementary steps. As a consequence, cascade reactions have revolutionized synthetic strategies and conceptual thinking. The authors highlight cyclization via carbopalladation and acylpalladation and Heck-pericyclic sequences. They discuss p-allyl palladium-based cascade reactions, Michael-type additions as an entry to transition-metal-promoted cyclizative transformations, and sequential or consecutive palladium-catalyzed processes, and show Pauson-Khand cascades, metal-catalyzed cyclizations of acyclic precursors, as well as cascade and sequential ruthenium-catalyzed transformations. Therefore, the reader finds overview of an exciting and highly dynamic field of a new and innovative methodological concept.
Ei-Ichi Negishi, Guangwei Wang, and Gangguo Zhu: Palladium-Catalyzed Cyclization via Carbopalladation and Acylpalladation -- Paultheo von Zezschwitz, and Armin De Meijere: Domino Heck-Pericyclic Reactions -- Nitin T. Patil, and Yoshinori Yamamoto: Palladium Catalyzed Cascade Reactions Involving p-Allyl Palladium Chemistry -- Geneviève Balme, Didier Bouyssi, and Nuno Monteiro: The Virtue of Michael-Type Addition Processes in the Design of Transition Metal-Promoted Cyclizative Cascade Reactions -- Thomas J. J. Müller: Sequentially Palladium Catalyzed Processes -- Javier Pérez-Castells: Cascade Reactions Involving Pauson-Khand and Related Processes -- Corinne Aubert, Louis Fensterbank, Vincent Gandon, and Max Malacria: Complex Polycyclic Molecules from Acyclic Precursors via Transition Metal-Catalyzed Cascade Reactions -- Christian Bruneau, Sylvie Dérien, and Pierre H. Dixneuf: Cascade and Sequential Catalytic Transformations initiated by Ruthenium Catalysts.
Keywords: Organometallic chemistry .; Catalysis; Inorganic chemistry; Organometallic Chemistry; Catalysis; Inorganic Chemistry